When Circularity Reinforces Extraction: Risks in Circular Economy Narratives - Arya, Apoorva; Bhutani, Arpit; Melembe, Eduardo; Ayappa, Tammanna (International Transitions, 2026)
This article critically examines how circular economy (CE) narratives risk perpetuating colonial extractivist patterns under the guise of new green branding, by illustrating how historical trade dependencies persist in contemporary CE policies. The case study centers on lithium mining in Bolivia. Employing a qualitative interpretivist research design that integrates archival and documentary research with discourse analysis, this study reveals that while sustainability discourses are promoted, they simultaneously rein-force the asymmetry between global north demand and global south resource supply. This dynamic positions the Global South as a provider of clean raw materials for northern circular economies. Although Evo Morales’ resource Nationalism aimed to assert national control over resources, it ultimately remained reliant on foreign expertise. Subsequently, CE narratives framed with green branding in Bolivia function less as agents of structural transformation and more as legitimizing discourses for continued external control. The analysis states that without decolonial approaches addressing local community concerns and environmental inequalities, CE transitions risk replicating extractive relations under the narrative of ecological modernization..